Typology of Peri-urban Agricultural Farms in Tahoua Region, Niger Republic - Mahamadou, Moussa dit Kalamou; Ludovic, Andres; Boubacar, Yamba; Philippe, Lebailly (European Scientific Journal, ESJ, 2022)
This article presents a typology of peri-urban farms in Tahoua region in Niger. It concerns also peri-urban households distributed according to the agro-ecological zones of this region. The results were obtained investigations carried out in five villages with 21 heads of household per village, which gives 105 heads of households located in urban communes of the Tahoua region. From the analysis of the results, the issues of urbanization in the rural sector, marital status, level of education, the capacity of granaries, the different food productions, the workforce and the composition in TBU per peri-urban areas emerge and agroecological. The Study will establish a diagnosis of these areas present around the secondary cities of Tahoua. The tests of normality and equality of variances allowed us to establish an ANOVA between peri-urban agro-ecological zones.